CO2 and water vapor-tolerant yttria stabilized bismuth oxide (YSB) membranes with external short circuit for oxygen separation with CO2 capture at intermediate temperatures - Zhang, K; Zou, Y.; Su, C.; Shao, Zongping; Liu, Lihong; Wang, Shaobin; Liu, Shaomin (Elsevier B.V, 2013)
Yttria stabilized bismuth oxide (YSB) membranes were prepared using a self-made YSB powder withsintering temperatures down to 750 °C. The membrane was characterized by SEM, porosity measurement, electrochemica limpedance measurement and composition detection by plasma-optical emission spectrometry. The prepared membranes were tested for air separation under a new concept in the field-pure ion conductor with external short circuit.The influences of CO2 and water vapor in the sweep gas on the O2 permeation behavior of the resultant YSB membranes have been investigated. The O2 permeation fluxes of the YSB membrane decreased with increasing the CO2 concentration in the sweep gas. Such flux decline is a very normal phenomenon due to the strong chemical adsorption of CO2 to the membrane surface. YSB can withstand the presence of CO2 atmospheres at high temperatures without causing any reaction between the two phases. More interesting is that, contrary to the negative effect of the water vapor on other membranes like perovskite, the presence of H2O is beneficial for O2 permeation through the YSB membrane. The maximum oxygen flux achieved was 1.33 ml cm-2 min-1 at 850 °C for the YSB membrane with a thickness of 1mm. Thin-film membrane technology and surface modification can help to further improve the O2 fluxes to be of practical interest.